Membangun Nilai Kasih Persahabatan dalam Pemberian Kerbau atau Babi dalam Upacara Rambu Solo’ - Yayu Astuti Lampi (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
Toraja One of the cultures that is popular for its exquisite culture both inside and outside of Indonesia. The Rambu Solo’ ceremony, a death event that is widely celebrated in Toraja, is one of the most well-known. There is a tradition in the ritual